Influence of doping on the optical properties of silicon nanocrystals embedded in SiO2. Issue 1 (26th November 2014) - Frégnaux, Mathieu; Khelifi, Rim; Le Gall, Yann; Muller, Dominique; Mathiot, Daniel
Abstract Co‐implantation, with overlapping implantation projected ranges, of Si and doping species (P, As, B) followed by a thermal annealing step is a viable route to form doped Si nanocrystals (NCs) embedded in SiO2. This presentation deals with optical characterizations of both doped and undoped Si‐NC prepared by this method. The NC effective presence in the oxide layer and their crystallinity is verified by Raman spectrometry. Photoluminescence (PL) and PL excitation measurements reveal quantum confinement effects and a gradual PL quenching with increasing dopant concentrations. The measured Stokes shift remains constant and its value ∼ 0.2 eV is almost twice the Si–O vibration energy. This suggests that a possible radiative recombination path is a fundamental transition assisted by a local phonon. Lifetime investigations show that PL time‐decays follow a stretched exponential. Atomic probe tomography analyses demonstrate that n‐type dopants (P, As) are efficiently introduced in the NC core, whereas p‐type dopant (B) are located at the NC/SiO2 interface. All together these experimental observations question on possible different carrier recombination paths in P or As doped NC compared to B one's. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)